2005
DOI: 10.21273/horttech.15.3.0642
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid Insecticide Slows Development of Phony Peach and Plum Leaf Scald

Abstract: Observations in controlled field experiments over 5 years indicated that imidacloprid, applied as a soil drench around the trunks of peach (Prunus persica), nectarine (P. persica var. nectarine) and japanese plum (P. salicinia) trees at planting and in the early spring and mid-summer for two subsequent seasons (0.7 g/tree a.i.), slowed the development of symptoms of phony peach disease (PPD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Between 1929 and 1947, PPD led to the loss of about 1,500,000 peach trees (Turner, 1949). To date, in the United States, PLS and PPD have caused an enormous economic damage, mainly in orchards in Florida and Georgia (Dutcher et al, 2005;Overall and Rebek, 2017).…”
Section: Plum and Peach Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 1929 and 1947, PPD led to the loss of about 1,500,000 peach trees (Turner, 1949). To date, in the United States, PLS and PPD have caused an enormous economic damage, mainly in orchards in Florida and Georgia (Dutcher et al, 2005;Overall and Rebek, 2017).…”
Section: Plum and Peach Treesmentioning
confidence: 99%
“…On sensitive plum cultivars "Methley" and "Santa Rosa, " many specimens of this insect are found during the summer (Andersen et al, 2008). A study showed that spraying imidacloprid onto the roots reduced the symptoms of PPD and PLS (Dutcher et al, 2005). In fact, imidacloprid is a systemic insecticide against H. vitripennis and many homopteran pests.…”
Section: Insect Vectors Of Xylella Fastidiosa On Prunus Spp Around the Worldmentioning
confidence: 99%
“…Imidacloprid, a systemic neonicotinoid insecticide, slows development of epidemics of PD in grapevine plantings (Krewer et al 2002), and was used in peach to determine if a soil drench at planting followed by consecutive applications for five seasons thereafter would reduce incidence or control PPD. Whereas 13.1% of the trees treated with imidacloprid developed symptoms of PPD, 71.4% of the untreated trees developed PPD (Dutcher et al 2005), indicating that annual use of imidacloprid could provide a useful level of control. Resistance to insecticides is a concern when applying chemicals, but there is little cross-resistance with older insecticide classes (Nauen and Denholm 2005;Denholm et al 2002).…”
Section: Control Of the Vectorsmentioning
confidence: 99%